2000
DOI: 10.1051/animres:2000128
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of digestible fibre by starch in the diet of the growing rabbit. II. Effects on performances and mortality by diarrhoea

Abstract: -The effects of the level of dietary starch on growth performance and mortality were studied in six experimental sites on 2 328 growing rabbits (582 per diet). Four iso-lignocellulosic (ADF) diets (A12, A16, A20, A24) with increasing starch content (12, 16, 20, 24%) instead of digestible fibre (hemicelluloses and pectins) were compared. Diets were given ad libitum from weaning (28 and 35 d old, depending on the site) to slaughter (between 68 and 71 d old). The increase (12 points) of dietary starch level led … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 11 publications
(15 reference statements)
3
27
0
2
Order By: Relevance
“…As discussed above (Effect of CP level) previous studies also showed that increasing the soluble fibre-to-starch ratio decreased rabbit mortality and morbidity Perez et al, 2000;Soler et al, 2004;Xiccato et al, 2008) and improved caecal environment with lower pH, higher VFA and lower N-ammonia production Gidenne and Bellier, 2000;Xiccato et al, 2008). The higher acetate proportion and lower butyrate rate were associated to a greater availability of substrate fermentable by fibrolytic bacteria (Falcã o-e-Cunha et al, 2004) and a lower activity of amylolytic microflora in the caecum (Parigi Bini et al, 1990;Blas and Gidenne, 2010).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…As discussed above (Effect of CP level) previous studies also showed that increasing the soluble fibre-to-starch ratio decreased rabbit mortality and morbidity Perez et al, 2000;Soler et al, 2004;Xiccato et al, 2008) and improved caecal environment with lower pH, higher VFA and lower N-ammonia production Gidenne and Bellier, 2000;Xiccato et al, 2008). The higher acetate proportion and lower butyrate rate were associated to a greater availability of substrate fermentable by fibrolytic bacteria (Falcã o-e-Cunha et al, 2004) and a lower activity of amylolytic microflora in the caecum (Parigi Bini et al, 1990;Blas and Gidenne, 2010).…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, rabbit mortality and morbidity increased as soluble fibre-to-starch ratio decreased in iso-ADF diets characterised by rather high-CP concentration (158 to 169 g/kg; Jehl and Gidenne, 1996;Perez et al, 2000;Soler et al, 2004;Xiccato et al, 2008). In contrast, there is no information about the effect of soluble fibre-to-starch ratio when feeding low-CP diets (,155 g/kg).…”
Section: Discussionmentioning
confidence: 99%
“…ADF) in a delay compatible with the retention time of the caeco-colic segment (9 to 13 h, Gidenne, 1997). The favourable effect of the DgF, compared with starch intake, was first demonstrated by Perez et al (2000) with four iso-ADF diets: mortality was significantly reduced when DgF replaced starch. According to the analysis presented in Figure 3a, the post-weaning mortality rate of the rabbit is globally reduced when DgF are included in iso-ADF diets (without antibiotic use), as seen in four studies out of six, although a large variability remained among the studies.…”
Section: Brief Overview Of Polymers Of the Plant Cell Wall: Definitiomentioning
confidence: 99%
“…However, to look more precisely at this effect, we should select studies comparing diets having a similar level of ADF (or NDF), as shown in Figure 9. However, even for the six studies selected (same data set as for Mortality, after weaning % Dietary SF*, % as fed basis Gidenne et al, 2013Trocino et al, 2010Soler et al, 2004Xiccato et al, 2011Xiccato et al, 2011Tazzoli et al, 2009Perez et al, 2000Gidenne et al, 2004aPerez et al, 1994Perez et al, 1996Gidenne et al, 2004bGidenne et al, 2001Bennegadi et al, 2001Debray et al, 2002De Blas et al, 1981Blas et al, 1994 [r² = -0.04] Figure 8 The post-weaning mortality of the growing rabbits is weakly related to the dietary soluble fibre (SF*) level. Data from 16 studies and 78 diets, without antibiotics, and without selection for the fibre level.…”
Section: Brief Overview Of Polymers Of the Plant Cell Wall: Definitiomentioning
confidence: 99%
“…Some studies have tried to address this problem by using varying sources of starch [9,13], to compare diets having similar levels of starch and other nutrients. However, the effects of starch nature on mortality by non-specific enteropathy have, to our knowledge never been studied using a powerful procedure, such as a network of experimental sites involved in studies on the role of dietary fibre/starch supply [12], in order to include a large number of rabbits in the experiment, and thus to assess more precisely the health status of the animal. Therefore, the establishment of recommendations on starch remains incomplete and it must be supported by experimental results, particularly to assess the potential effects of the cereal sources on mortality by digestive troubles.…”
Section: Introductionmentioning
confidence: 99%